Magnitude and determinants of animal source food consumption among children aged 6-23 months in Ethiopia: secondary analysis of the 2016 Ethiopian demographic and health survey - Gebretsadkan Gebremedhin Gebretsadik; Amaha Kahsay Adhanu; Afework Mulugeta (BMC, 2022)
Abstract Background Undernutrition puts children in a physical and cognitive disadvantage. Animal source foods (ASFs) are important components of nutritious diets and play a significant role in increasing dietary diversity and minimizing the risk of undernutrition among children. Ethiopia still suffers from child undernutrition and there's no adequate information regarding consumption of ASFs. The objective of this study was to determine the magnitude and determinanats of ASF consumption among children 6-23 months of age. Methodology A total weighted sample of 2861 children drawn from the 2016 Ethiopian demographic and health survey was analyzed using "SVY" command of STATA 14.0. Multivariable logistic regression was used to determine the independent determinants of ASF consumption. The strength of the association was measured by odds ratio and 95% confidence interval and p-value < 0.05 was considered statistically significant. Results Nearly half (46.5%) of the children reported consuming any type of ASF. Religion, child age, number of household assets, number of livestock owned by a household, and ownership of land usable for agriculture were significant determinants of the outcome variable. The odds of ASF consumption were six times, twice, and 70% lower in orthodox children compared to other (catholic, traditional, or others), muslim, and protestant children, respectively. Household ownership of assets and livestock led to an increase in consumption of ASF by 19 and 2%, respectively. Children aged 18-23 months were more likely to consume ASF as compared to the younger age group (6-8 months old children). In the contrary, children from households that own land usable for agriculture were 33% less likely to consume ASFs as compared to those from households that do not own. Conclusions In Ethiopia, only nearly half of children aged 6-23 months consume any type of ASF. The findings of this study imply that ASF consumption can be increased through integrated actions that involve community and religious leaders and programs focused on empowering households' capability of owning other socioeconomic entities including assets and livestock. This study also may contribute to the growing body of research works on the importance of ASF provision in preventing child undernutrition.